Preliminary study of neurofilament light chain as a biomarker for hypoxia-induced neuronal injury in dogs - Yun, Taesik; Chae, Yeon; Koo, Yoonhoi; Lee, Dohee; Kim, Hakhyun; Yang, Mhan-Pyo; Kang, Byeong-Teck (Frontiers in Veterinary Science, 2023)
Neurofilament light chain (NfL) is a neuroaxonal protein in the nervous system. NfL has recently been demonstrated to be a biomarker for various neurological diseases. In this study, we investigated the potential role of NfL in hypoxia-induced neuronal injury in dogs. Serum NfL levels were determined using a single-molecule array. Serum NfL concentrations were significantly higher in hypoxemic dogs without neurological signs (n=6, 175.5 pg/mL) than in healthy dogs (n=15, 15.9 pg/mL; P < 0.0001). Therefore, neuronal injury should be considered in dogs with hypoxemia caused by cardiopulmonary diseases, even in the absence of neurological signs.